Poly – β – Hydroxybutyrate (PHB) - Plastics from bacteria and for bacteria - Priya Iyer*, Rebeca Robert and (Journal of Ecobiotechnology, 2011)
<span style="font-size: 10pt; line-height: 110%; font-family: ";Garamond";,";serif";; mso-fareast-font-family: SimSun; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;">Bacillus subtilis<span style="font-size: 10pt; line-height: 110%; font-family: ";Garamond";,";serif";; mso-fareast-font-family: SimSun; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;"> was found to produce PHB and the amount of PHB produced was estimated under various conditions like pH, temperature, and also using different substrates. PHB was also produced using various inexpensive substrates like arrowroot powder; rice water: and sago water and the amount of PHB produced were estimated by reading the absorbance at 235nm.